Kualitas Dan Fertilitas Spermatozoa Sebagai Akibat Pejantan Berbeda - Mohamad Ervandi; Widiastuti Ardiansya; Sandi Prahara (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
The purpose of this research was to determine the effect of chicken species on the quality and fertility of spermatozoa. Semen is collected from Kampung, Arab, and Bangkok chickens through a massage method. The semen obtained is collected in a test tube, then diluted with Ringer's Dextrose. Spermatozoa examination is carried out macroscopically and microscopically. There are eighteen (18) female leghorn chickens used to test the fertility of spermatozoa, through the process of hatching eggs in an incubator. The research design used a Completely Randomized Design (CRD), with three (3) treatments and six (6) replications. Data analysis using analysis of variance, if there are differences, continued with the Least Significant Difference test (LSD). The results showed that the fertility of Bangkok chicken spermatozoa was significant (P 0.01) compared to the sperm fertility of Arab chickens and Kampung chickens. The average fertility value of each cement is Kampung chicken: 68.88%, Arabic chicken: 71.32%, Bangkok chicken: 89.96%. The quality of Bangkok chicken semen is better than native chicken and Arabic chicken